2015
DOI: 10.4103/2230-8210.152781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetic education on the knowledge, attitude and practices of diabetic patients towards prevention of hypoglycemia

Abstract: Aims:To assess the role of diabetic education in increasing awareness about hypoglycemia and decreasing hypoglycemic symptoms in diabetics.Materials and Methods:This is a longitudinal study involving the use of a structured questionnaire for obtaining baseline information related to knowledge, attitude and practices (KAP) of diabetic patients regarding hypoglycemia. Then the patients were given diabetic education by the treating doctor regarding hypoglycemia, its symptoms and prevention; the effect of which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 3 publications
3
16
0
1
Order By: Relevance
“…In addition, the overall situation regarding MNT was not optimal, with the mean percentage scores for each of KAP, K, A and P being 47.79%, 44.83%, 41.00%, and 51.70%, respectively. As reported by Bhutani et al, KAP could be significantly improved following the provision of diabetes‐related education. Indeed, we observed similar results.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, the overall situation regarding MNT was not optimal, with the mean percentage scores for each of KAP, K, A and P being 47.79%, 44.83%, 41.00%, and 51.70%, respectively. As reported by Bhutani et al, KAP could be significantly improved following the provision of diabetes‐related education. Indeed, we observed similar results.…”
Section: Discussionmentioning
confidence: 68%
“…Hypoglycemia is a true medical emergency [1] and has a critical effect on mortality, morbidity, and quality of life [2]. Hypoglycemia is a major barrier for attaining treatment goals and reduction of long-term complications in diabetes management and therefore it is an important reason for increased costs of medical care [3].…”
Section: Introductionmentioning
confidence: 99%
“…Bhutani et al found improved knowledge, attitude and practices and fewer symptomatic hypoglycaemia episodes in T2D patients after structured education with their doctor. 21 There is substantial evidence that education is key in improving diabetes management, especially in reducing hypoglycaemia. 4,[22][23][24][25] We found that CSII use was associated with higher rates of safer responses to hypothetical pre-bed BG levels.…”
Section: Discussionmentioning
confidence: 99%